Nouméa: a new multi-mission calibration and validation site for past and future altimetry missions? - Chupin, Clémence; Ballu, Valérie; Testut, Laurent; Tranchant, Yann-Treden; Aucan, Jérôme (Ocean science, 2023)
Today, monitoring the evolution of sea level in coastal areas is of importance, since almost 11 % of the world's population lives in low-lying areas. Reducing uncertainties in sea level estimates requires a better understanding of both altimetry measurements and local sea level dynamics. In New Caledonia, the Nouméa lagoon is an example of this challenge, as altimetry, coastal tide gauge, and vertical land motions from global navigation satellite systems (GNSSs) do not provide consistent information. The GEOCEAN-NC 2019 field campaign addresses this issue with deployments of in situ instruments in the lagoon (GNSS buoy, pressure gauge, etc.), with a particular focus on the crossover of one Jason-series track and two Sentinel-3A missions tracks. In this study, we propose a method to virtually transfer the Nouméa tide gauge at the altimetry crossover point, using in situ data from the field campaign. Following the philosophy of calibration and validation (Cal/Val) studies, we derive absolute altimeter bias time series over the entire Jason and Sentinel-3A periods. Overall, our estimated altimeter mean biases are slightly larger by 1–2 cm compared to Corsica and Bass Strait results, with inter-mission biases in line with those of Bass Strait site. Uncertainties still remain regarding the determination of our vertical datum, only constrained by the three days of the GNSS buoy deployment. With our method, we are able to re-analyse about 20 years of altimetry observations and derive a linear trend of −0.2 ± 0.1 mm yr−1 over the bias time series. Compared to previous studies, we do not find any significant uplift in the area, which is more consistent with the observations of inland permanent GNSS stations. These results support the idea of developing Cal/Val activities in the lagoon, which is already the subject of several experiments for the scientific calibration phase of the SWOT wide-swath altimetry mission.